Separation of Co(II), Mn(II) and Ni(II) from the sulfuric acid leaching solution of lithium-ion battery by solvent extraction: Solvent extraction separation of Co(II), Mn(II) and Ni(II) - Lee, Manseung; Jeon, Ji Hyeok; Wen, Jiang Xian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Lithium-ion batteries(LIBs) contain valuable metals such as cobalt, lithium, manganese, and nickel. Therefore, recycling of spent LIBs is important to meet the demand for the above-mentioned metals. In combined process for the treatment of spent LIBs, smelting reduction of LIBs results in metallic alloys containing cobalt, manganese, nickel, and a small amount of other metals. These metallic alloys can be dissolved using sulfuric acid solutions containing oxidizing agents. In this work, solvent extraction experiments were done to separate Co(II), Mn(II), and Ni(II) from synthetic sulfate solution, the composition of which was similar to the leaching solutions of spent LIBs. The concentrations of Co(II), Mn(II) and Ni(II) in the sulfate solutions were 2, 0.3, and 8 g/L, respectively. First, it was possible to completely separate Mn(II) from Co(II) and Ni(II) by selective extraction using two stages of counter-current extraction with 10% saponified 0.3 M D2EHPA. Then, pure MnSO4 solution was recovered by stripping the loaded D2EHPA with 0.05 M H2SO4 solution. From the Mn(II) free raffinate, Co(II) was completely separated over Ni(II) by two stages of counter-current extraction with 15% saponified 0.3 M Cyanex 272. The purity of Ni(II) in the raffinate was higher than 99.9% and pure CoSO4 solution was recovered by stripping the loaded Cyanex 272 with 0.05 M H2SO4 solution. A process on the basis of solvent extraction with commercial organophosphorus extractants was proposed to recover pure CoSO4, MnSO4, and NiSO4 solutions from the sulfuric acid leaching solutions of spent LIBs.
Keywords: hydrometallurgy, lithium-ion batteries, recycling, separation, solvent extraction